Evaluation of the economic viability of the application of a trigeneration system in a small hotel. Issue 1 (31st March 2016) - Afonso, Clito; Rocha, Carlos
Abstract: Energy is an indispensable factor for any human activity. Transport, industrial production, trade, communications, etc. depend on the energy availability. Traditionally, consumers meet their energy demand by buying separately electricity and fuel to the distribution companies. With regard to electric energy generation acquired by consumers, a good portion is produced in conventional thermoelectric power plants. In modern power plants, the total losses in energy can go up to 52.5 % without any kind of recovery. Thermal energy is obtained from the fuel purchased by consumers in burning systems with a maximum average efficiency, at best, about 90 % (10 % lost). Faced with this problem arises the need to increase the efficiency of electricity production processes and heat generation in order to reduce the financial and environmental costs. Thus, as an alternative to large conventional power plants, decentralized production of electricity arises, and, in particular cogeneration, in order to take advantage of the inherent limitations of the conversion of heat into work. CHP (Combined Heat and Power) is a combined process of production and exploitation of thermal energy and electricity, in an integrated system, from the same primary source. In spite of not being a new technology its applications are mainly used in the industry. These kind of systems contributes also for a decrease of CO2 emissions to the environment. The aim of this study is to analyse the technical and economic potential of a real situation in a small hotel located in a city of Portugal. Instead of using only a CHP, the generated heat was also used for cooling - CHCP (Combined Heat, Cooling and Power). For that, besides the energetic analysis carried out, a detailed economic analysis was done in order to evaluate its feasibility and risk regarding the main parameters to be taken in account, namely the NPV (Net Present Value), IRR (Internal Rate of Return), Payback Period and PES (Primary Energy Savings) and Avoided Emissions (AE) of CO2 . The main conclusions obtained are that the CHCP contributes to a PES of 57 tep/year, the AE being 68 teq CO2 /year. The payback period is 3.6 years.